Infection and infective endocarditis after cardiac implantable electronic device implantation: a contemporary nationwide cohort study. (19th May 2022) - Maille, B; Defaye, P; Boveda, S; Herbert, J; Pierre, B; Deharo, JC; Fauchier, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Aims: To determine the contemporary incidence and risk factors of infection and infective endocarditis (IE) following implantation of a first-time, permanent, cardiac implantable electronic device (CIED). Methods: This French longitudinal cohort study was based on the national hospitalization database covering hospital care from for the entire population. All adults (age ≥18 years) hospitalized in French hospitals from January 1, 2010 to December 31, 2019, who underwent a de novo permanent pacemaker (PM) or implantable cardioverter defibrillator (ICD) implantation were identified together with the occurrence of post-implantation infection and IE-events during follow-up. Results: In total 688, 007 CIED patients with de novo implants were identified (single-chamber pacemaker 18.8%, dual-chamber pacemaker 64.9%, cardiac resynchronization therapy [CRT]pacemaker 3.2%, single-chamber ICD 4.3%, dual-chamber ICD 3.4%, CRT ICD 5.5%). Follow-up was 2.6±2.6 years (median 1.9, IQR 0.2-4.3 years) and total follow-up time was 1, 788, 166person-years (PYs). There were 9, 804 patients with CIED-related infection during follow-up (incidence rate 5.48 per 1000 patient.year) among whom 2, 658 had IE (incidence rate 1.49 per 1000 patient.year). The incidence rate (per 1000 PYs) of CIED-related infection and IE in the different subgroups of patients with pacemakers and ICD (single-chamber, dual-chamber, CRT) are in table 1. Incidence rates were higher in patients with an ICD than in those with a pacemaker, and higher in those with CRT. Incidence rates of CIED-related infection and IE were not different in single-chamber vs dual-chamber CIEDs(table 1). In multivariable analysis, ICD (vs pacemaker, HR: 1.59; 95% CI 1.40-1.80) and CRT (vs no CRT, HR: 1.21; 95% CI: 1.07-1.37) were independent risk factors for CIED-related infection. Dual-chamber pacemakers were not associated with a higher risk of CIED-related infection than single-chamber pacemakers. Similarly, dual-chamber ICDs were not associated with a higher risk of CIED-related infection than single-chamber ICDs (table). There were similar findings when analysing the risk of IE during FU. ICD (vs pacemaker, HR: 1.31; 95% CI 1.23-1.40) and CRT (vs no CRT, HR: 1.24; 95% CI: 1.16-1.32) were independent risk factors for IE. Dual-chamber pacemakers were not associated with a higher risk of IE than single-chamber pacemakers and dual-chamber ICDs were not associated with a higher risk of IE than single-chamber ICDs (table). Results were similar when one considered separately the periods 2010-2014 and 2015-2019 Conclusion: The risk of CIED-related infection and IE was significantly higher in patients with ICDs than in those with pacemakers and significantly higher with CRT than with no CRT. By contrast, there was no statistical difference in the risk of CIED-related infection and IE in patients with single-chamber or dual-chamber CIEDs in this contemporary analysis at a nationwide level.